Study of Mathematical Reasoning Ability for Mathematics Learning in Schools: A Literature Review - Marasabessy, Rosida (Indonesian Journal of Teaching in Science, 2021)
This article aims to examine students' mathematical reasoning abilities. This study is in the form of using approaches and strategies for improving students’ abilities. Differences in mathematical reasoning abilities were revealed from a gender perspective, teaching materials oriented towards mathematical reasoning, teacher perceptions, and design of teacher action characteristics to improve the process of students' mathematical reasoning. Scientific articles are studied to collect information about students' mathematical reasoning. The study results indicate: 1) learning strategies such as open-ended, visual basic application for excel, adversity question, and argument-driven inquiry could be used to improve students' mathematical reasoning abilities. 2) the development of male students' mathematical reasoning was significantly better than female students. 3) teachers' perceptions of mathematical reasoning differ from the perceptions of experts. 4) the quality of students' mathematical reasoning is still dominated by imitative reasoning. 5) The ability to generalize and justify will emerge if the teacher designs a challenging lesson for students followed by activities to guide students. This research is expected to be helpful in education, especially mathematics learning in schools, where it can be used as a reference for choosing strategies and teacher reading materials to improve students' mathematical reasoning abilities.